KESALAHAN BERBAHASA BIDANG FONOLOGI PADA VIDEO YOUTUBE “HELLO JADOO” DUBBING INDONESIA - Khasanah, Farinda (Hasta Wiyata, 2024)
Language is the main tool used by humans to communicate and interact in everyday life. Language develops and changes over time according to the needs and dynamics of society. With language humans can convey ideas, feelings, and information with others in everyday life. Language errors can occur in spoken form. Dubbing or substituting voices in different languages on the Youtube video of the animated cartoon "Hello Jadoo" into Indonesian there are 12 language errors in the field of phonology. The research method used in this study is qualitative descriptive. With the data collection techniques used, namely listening and recording techniques. The most phonological errors in the Youtube video of the animated cartoon "Hello Jadoo" dubbed Indonesian are 11 phoneme reductions. A language error must be corrected especially since the cartoon is widely watched by children. In the hope of dubbing, the use of Indonesian to conform to language norms and conventions. This includes word selection, sentence structure, and vocabulary that young audiences can understand